Obtaining the mean relative weights of the cost of care in Catalonia (Spain): retrospective application of the adjusted clinical groups case‐mix system in primary health care. Issue 2 (27th March 2012) - Sicras‐Mainar, Antoni; Velasco‐Velasco, Soledad; Navarro‐Artieda, Ruth; Jodar, Alba Aguado; Plana‐Ripoll, Oleguer; Hermosilla‐Pérez, Eduardo; Bolibar‐Ribas, Bonaventura; Prados‐Torres, Alejandra; Violan‐Fors, Concepción
Abstract: Objective The study aims to obtain the mean relative weights (MRWs) of the cost of care through the retrospective application of the adjusted clinical groups (ACGs) in several primary health care (PHC) centres in Catalonia (Spain) in routine clinical practice. Methods This is a retrospective study based on computerized medical records. All patients attended by 13 PHC teams in 2008 were included. The principle measurements were: demographic variables (age and sex), dependent variables (number of diagnoses and total costs), and case‐mix or co‐morbidity variables (International Classification of Primary Care). The costs model for each patient was established by differentiating the fix costs from the variable costs. In the bivariate analysis, the Student's t, analysis of variance, chi‐squared, Pearson's linear correlation and Mann–Whitney–Wilcoxon tests were used. In order to compare the MRW of the present study with those of the United States (US), the concordance [intraclass correlation coefficient (ICC) and concordance correlation coefficient (CCC)] and the correlation (coefficient of determination: R 2 ) were measured. Results The total number of patients studied was 227 235, and the frequentation was 5.9 visits/habitant/year) and with a mean diagnoses number of 4.5 (3.2). The distribution of costs was €148.7 million, of which 29.1% were fixed costs. The mean total cost per patient/year was €654.2 (851.7), which was considered to be the reference MRW. Relationship between study‐MRW and US‐MRW: ICC was 0.40 [confidential interval (CI) 95%: 0.21–0.60] and the CCC was 0.42 (CI 95%: 0.35–0.49). The correlation between the US MRW and the MRW of the present study can be seen; the adjusted R 2 value is 0.691. The explanatory power of the ACG classification was 36.9% for the total costs. The R 2 of the total cost without considering outliers was 56.9%. Conclusions The methodology has been shown appropriate for promoting the calculation of the MRW for each category of the classification. The results provide a possible practical application in PHC clinical management.